2023
DOI: 10.1002/lio2.1097
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of thymoquinone in head and neck squamous cell carcinoma: A scoping review

Kera Kwan,
Albert Y. Han,
Laith Mukdad
et al.

Abstract: ObjectiveThymoquinone (TQ), the active constituent of Nigella sativa, has been shown to have anticancer effects in head and neck squamous cell carcinoma (HNSCC). This review aims to outline the properties of TQ, the known drivers in HNSCC formation, and summarize the anticancer effects of TQ in SCC.Data SourcesThree databases (PubMed, Embase, and Google Scholar) were queried for the key words “thymoquinone squamous cell carcinoma.”Review MethodsPublications that were not original research and publications that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
(269 reference statements)
0
2
0
Order By: Relevance
“…Thymoquinone, the main constituent of N. sativa , inhibits the proliferation, migration, and invasion and induces apoptosis by inhibiting the PI3K/Akt pathway activity in KB cell lines [ 23 ]. Thymoquinone is reported to have modified the PI3k/Akt pathway through reduced phosphorylation, also it leads to upregulation of tumor suppressor protein phosphatase and tensin homolog (PTEN) [ 24 ]. It is reported that thymoquinone at different concentrations reduced neuroinflammation by inhibiting TNF-α, IL-1β inflammatory mediators nitric oxide, and prostaglandin E2 (PGE2).…”
Section: Discussionmentioning
confidence: 99%
“…Thymoquinone, the main constituent of N. sativa , inhibits the proliferation, migration, and invasion and induces apoptosis by inhibiting the PI3K/Akt pathway activity in KB cell lines [ 23 ]. Thymoquinone is reported to have modified the PI3k/Akt pathway through reduced phosphorylation, also it leads to upregulation of tumor suppressor protein phosphatase and tensin homolog (PTEN) [ 24 ]. It is reported that thymoquinone at different concentrations reduced neuroinflammation by inhibiting TNF-α, IL-1β inflammatory mediators nitric oxide, and prostaglandin E2 (PGE2).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome measure was the size of the lesion at 3 months post-treatment compared to the initial dimensions. Although the study was completed in 2020, the results have not yet been published [ 156 , 157 ].…”
Section: Tq and Colorectal Cancermentioning
confidence: 99%